PENGARUH EKSTRAK DAUN KUNYIT (Curcuma longa Linn.) SEBAGAI INSEKTISIDA ELEKTRIK TERHADAP MORTALITAS NYAMUK Culex sp. L. - Aseptianova Aseptianova (Jurnal Pro-Life, 2019)
Mosquito Culex sp. L. is a vector of elephantiasis disease, prevention effort of elephantiasis vector is usually done by using chemical and natural insecticide. In the leaves of turmeric can be used as a natural insecticide in the prevention of elephantiasis vector disease. The objectives of this research are (1) to know the effect of turmeric extract ((Curcuma longa Linn.) As electrical insecticide to mortality of Culex sp. L. (2) To know the concentration of turmeric extract (Curcuma longa Linn.) Which is effective to be used as an electric insecticide against mortality of Culex sp. L. expressed by the toxicity test of LC50 and LT50. The method used in this research is an experimental method with Completely Randomized Design (RAL) which consists of 5 treatments and 4 replications. Based on research result of turmeric extract (Curcuma longa Linn.) Have a very significant effect on mortality of Culex sp. L. with sig value 0,000 <sig value. 0.05. The probit analysis of LC50 of turmeric leaves extract on mortality of Culex sp. L. is 44, 840 ml, meaning that at that concentration has occurred 50% mortality of total mosquito. The probit analysis of LT50 turmeric leaves extract on mortality of Culex sp. L. for 1.825 hours. Keywords: turmeric leaves extract, mortality Culex sp. L. mosquito